Migration Spurs Changes in the Human Microbiome: A Review. (14th June 2022) - Shad, Nayeli; Cunningham, Solveig; Shaikh, Nida
Abstract: Objectives: Immigrants' health may deteriorate when moving from a non-Western to a Western country due to acculturation and environmental differences. The microbiome appears to play a large role in human health: dysbacteriosis may cause disease predisposition. Thus, we investigated the relationship between migration and microbiome composition. Methods: We conducted a systematic review using microbiome- and migration-related search terms in PubMed and Web of Science. We included articles examining the gut, oral, and oropharyngeal microbiome in people who migrated internationally. Results: Ten articles met eligibility criteria. Three articles found a difference in the microbiome of migrants compared with other residents of their country of birth, four found differences associated with duration of stay in the country of resettlement, and six found differences compared with the native-born population in the country of resettlement. Conclusions: The results suggest that migration is associated with a change in features of the microbiome,  specifically bacterial diversity or richness and species makeup. Microbiome composition additionally varied with age at migration, time since migration, and country of resettlement. Funding Sources: This work was supported in part by the National Institutes of Health Grant R25 DK078381.